Polyurethanes Based on Environmentally Friendly Polyols as a Promising Alternative to HTPB Binder for Composite Propellant Rockets - Sorin-Viorel Dolana; Anamaria Zaharia; Tanţa-Verona Iordache; Andrei Sârbu; Celina-Maria Damian; Traian Rotariu; Anita-Laura Chiriac; Ana-Mihaela Gavrilă; Anton Ficai (Proceedings)
Composite propellants used in solid-fuel rockets commonly consists of an oxidizer, the most used being ammonium perchlorate, fuels such as powdered aluminum, compounds that control the burn rate (catalysts or inhibitors), and various other additives [...]